A Potential Maternal Fatality Averted: The Case of a Young Patient who Underwent a Peripartum Hysterectomy at a District Hospital : DOI: https://doi.org/10.46405/ejms.v6i9.536 - Rimal , Goma; Khadka , Shishir (Europasian Journal of Medical Sciences, 2024)
The case reviewed here represents a 22-year-old gravida-two woman who lived in a relatively more accessible hill town in Nepal. It was determined to be a potentially fatal case, and a peripartum hysterectomy was performed on her. The potential fatality was averted due to the availability of an obstetrician/gynecologist, an anesthesiologist, a functioning blood bank and blood transfusion facility, and nurses and other support staff. The case underscores that PPH could happen to any pregnant woman without any identifiable risk factor, and second, averting a potential maternal death requires the whole health system to function effectively.